Digital Literacy and Critical Thinking Skills of Physics Education Students: An Empirical Analysis and Educational Implications - Ana Silfiani Rahmawati; Ida Hamidah; Achmad Samsudin; Diana Rochintaniawati (Yayasan Pendidikan Bima Berilmu, 2026)
This study aims to examine the levels of digital literacy and critical thinking skills among physics education students as prospective science educators, as well as to provide an empirical basis for improving instructional practices. A quantitative descriptive approach was used, involving 31 undergraduate students through a purposive sampling technique. Data were collected using validated instruments consisting of a digital literacy test based on five competency areas-information and data literacy, communication and collaboration, digital content creation, digital safety, and problem solving and a critical thinking test covering five indicators: focusing on questions, analyzing arguments, inductive reasoning, deductive reasoning, and evaluating definitions. The results indicate that both digital literacy and critical thinking skills are categorized as low. Students demonstrate relatively higher performance in communication and collaboration (28.3%) and deductive reasoning (24.1%), while the lowest achievements are observed in digital content creation and digital problem-solving (15.1%), as well as inductive reasoning (12.2%). These findings suggest that students tend to function as passive users of digital technology, with limited ability to critically evaluate information and construct knowledge. This study contributes to the field of physics education by providing an integrated profile of digital literacy and critical thinking within a specific disciplinary context. The findings underscore the urgent need for pedagogical innovations, particularly technology-integrated and inquiry-based learning approaches, to enhance higher-order thinking skills in the digital learning environment.